2021
DOI: 10.1155/2021/6693446
|View full text |Cite
|
Sign up to set email alerts
|

Oblique Lateral Interbody Fusion versus Transforaminal Lumbar Interbody Fusion in Degenerative Lumbar Spondylolisthesis: A Single-Center Retrospective Comparative Study

Abstract: Objective. To compare the efficacy of oblique lateral interbody fusion (OLIF) and transforaminal lumbar interbody fusion (TLIF) in single-level degenerative lumbar spondylolisthesis (DLS). Methods. A retrospective analysis of patients who underwent single-level DLS surgery in our department from 2015 to 2018 was performed. According to the surgical method, the enrolled patients were divided into two groups, namely, the OLIF group who underwent OLIF combined with percutaneous pedicle screw fixation (PPSF) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 40 publications
2
32
0
Order By: Relevance
“…Percutaneous pedicle screw is another widespread fixation technique with traditional trajectory, but its merits of minimally invasiveness popularized its utility in OLIF, OLLIF, LLIF and MIS-TLIF etc. OLIF takes an anterior retroperitoneal approach surgery through a small incision (42). Within the retroperitoneal space, surgeons will drag the psoas muscle backward, expose the intervertebral space between the psoas muscle and the abdominal aorta, and then perform decompression plus fusion, which is usually followed by posterior fixation of percutaneous pedicle screw.…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous pedicle screw is another widespread fixation technique with traditional trajectory, but its merits of minimally invasiveness popularized its utility in OLIF, OLLIF, LLIF and MIS-TLIF etc. OLIF takes an anterior retroperitoneal approach surgery through a small incision (42). Within the retroperitoneal space, surgeons will drag the psoas muscle backward, expose the intervertebral space between the psoas muscle and the abdominal aorta, and then perform decompression plus fusion, which is usually followed by posterior fixation of percutaneous pedicle screw.…”
Section: Discussionmentioning
confidence: 99%
“…These approaches provide direct access to the vertebral column, thereby effectively avoiding injury to the posterior muscle [ 3 ]. Moreover, ALIF and OLIF are applicable to improve endplate preparation for arthrodesis, shorten operation time, and reduce amount of blood loss compared with the traditional posterior approaches [ 4 , 5 ]. Although these two approaches cannot realize direct neural decompression, they can achieve indirect decompression by restoring disc height, foraminal height, and foraminal area, and their clinical effects have been broadly confirmed [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, at present, few scholars have applied OLIF in the treatment of spinal TB. In our previous study, we found that OLIF combined posterior internal fixation in the treatment of degenerative lumbar spondylolisthesis has the advantages of less surgical invasion, better decompression effect and faster postoperative recovery (including back pain and lumbar function) compared with the posterior approach surgery [ 11 ]. Thus, we wanted to know whether these positive results of OLIF could be extended to patients with lumbar TB.…”
Section: Introductionmentioning
confidence: 99%